Liderança em tempos de crise: lições de líderes mulheres sobre os desafios enfrentados na pandemia da covid-19 - Freitas, Núbia Jacqueline Pinheiro de (2023)
The pandemic caused by Covid-19 at the beginning of 2020 aroused the need for organizations to seek adaptive alternatives for their businesses, as the reality that presented itself consisted of an unforeseen scenario for the coming times, given that, in just three months, all continents were affected, resulting in economic and social insecurity for millions of people around the world. In this context, women were challenged in different ways, especially those who held leadership positions. Thus, the research problem that guided this study was: how did female leaders act during the Covid-19 pandemic in terms of their leadership experiences? Based on this question, this dissertation aims to analyze the experiences of female leaders in the work context to face the challenges posed by the Covid-19 pandemic. For the theoretical foundation of this research, studies are presented on the development of leadership theories, highlighting the main styles, approaches and stages of leadership. Finally, theoretical paths were covered that support notions about coping with crises in a professional context and about the role of women in the corporate environment in relation to leadership. Regarding methodological procedures, the research was developed using a qualitative approach, with semi-structured interviews carried out with 10 (ten) women leaders, with the research corpus being subjected to the content analysis technique. From data analysis, patterns and similarities were identified in the experiences lived by the interviewees, with a view to contributing to the understanding of a current and relevant phenomenon. Thus, the main results point to four final categories: (1) Challenges for leadership in crisis contexts; (2) Women leaders in the context of the crisis; (3) The challenging context; and (4) Lessons for leadership in times of crisis. These categories bring together a set of themes about women leaders which contribute to understanding the challenges and ways of coping faced by the women researched, encouraging a deeper understanding of the causes of the inequalities they experience. As a potential contribution, this research also offers a joint vision of the leaders interviewed here about themselves regarding the challenges of leadership for women when facing a general crisis situation, in addition to personal crises, which may instigate actions to promote goal 5.5 of SDG-5, of the 2030 agenda, which aims to: “Ensure the full and effective participation of women and equal opportunities for leadership at all levels of decision-making in political, economic and public life”. As a technological product, we propose a course on “Leadership Training and Development in Times of Crisis”, offered on the Sympla platform by the author of the dissertation.